Prescribing Patterns of Antibiotics and Sensitivity Patterns of Microorganisms towards Different Antibiotics in Multidisipinary Health Care Hospital - K, Khavane (International Journal of Pharmaceutical & Biological Archive, 2010)
Information about antibiotic use and resistance patterns of common microorganisms are lacking in hospitals in India. Excessive and inappropriate use of an antibiotic contributes to the development of bacterial resistance. This study was carried out to collect relevant demographic information, antibiotic prescribing patterns and the common organisms isolated including their antibiotic sensitivity patterns. The study of prescribing patterns seeks to monitor, evaluate and suggest modifications in practitioners prescribing habits so as to make medical care rational and cost effective. Antibiotic resistance is becoming a problem in the internal medicine ward. Formulation of a policy for hospital antibiotic use and an educational programme especially for junior doctors is required.